Metagenomic exploration of the virome of Rhipicephalus sanguineus ticks from Chachoengsao, Thailand - Saba Villarroel, Paola Mariela; Piorkowski, Geraldine; Laojun, Sedthapong; Liégeois, Florian; Gumpangset, Nuttamonpat; Missé, Dorothée; Chaiphongpachara, Tanawat; Wichit, Sineewanlaya (Frontiers in Microbiology, 2026)
Ticks are obligate blood-feeding ectoparasites that harbor a wide diversity of microorganisms. Rhipicephalus sanguineus, the brown dog tick, is globally distributed and poses significant veterinary and public health concerns due to its close association with companion animals and its occasional infestation of humans. However, the virome of this species in Thailand remains poorly characterized. In this study, we employed DNA Nanoball sequencing to investigate the virome of 80 R. sanguineus ticks, grouped into five pools, collected from dogs in Chachoengsao Province, Thailand, in 2023. Three viruses were identified: Brown dog tick phlebovirus 2 (BDTPV2), Changping tick virus 2 (CpTV-2), and Bole tick virus 4 (BLTV4), all detected in male ticks. These results highlight the need for further investigation into the ecological roles and biological significance of these viruses. Overall, our findings provide an updated perspective on the R. sanguineus virome in Thailand and underscore the importance of continued surveillance of tick-associated viruses within the One Health framework.